Penghitungan Suara Pilkada Gubernur Lampung dengan Metode Quick Count Berbasis SMS - Imam Asrowardi; Eko Subyantoro; Tri Sandhika Jaya (Politeknik Negeri Lampung, 2010)
General election is one of democracy party in Indonesia. Recently, local election also applies direct voting by the people. Quick count method was developed by using sampling data as comparison to find out the result of local elections rapidly. SMS can be used to deliver data directly to a computerized system so that the voting data with quick count method would be accumulated faster and presented automatically by the system. Besides, quick count data collection with SMS will also expand the processed data sampling.Â Keyword: SMS system, quick count, system, Automatic